2010
DOI: 10.1111/j.1532-849x.2009.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Assessment of an Intraoral Dental Colorimeter

Abstract: Within the limitations of this study, the intraoral colorimeter exhibited successful in vivo repeatability; however, the color difference detection performance of the device varied depending on the translucency of the specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…Although statistically significant differences were observed between groups, it has been accepted that a E value of 3.5 or greater is considered clinically significant. 41 The groups closest to this value were the control group A and brush only group C, where the color difference ( E) was 3.54. These findings can be further explored by more long-term clinical studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although statistically significant differences were observed between groups, it has been accepted that a E value of 3.5 or greater is considered clinically significant. 41 The groups closest to this value were the control group A and brush only group C, where the color difference ( E) was 3.54. These findings can be further explored by more long-term clinical studies.…”
Section: Discussionmentioning
confidence: 94%
“…The a* readings were slightly increased for the acid+brush group D, which indicates a shift from redness to greenness with increase in the a* value. Although statistically significant differences were observed between groups, it has been accepted that a ΔE value of 3.5 or greater is considered clinically significant . The groups closest to this value were the control group A and brush only group C, where the color difference (ΔE) was 3.54.…”
Section: Discussionmentioning
confidence: 99%
“…Karaagaclioglu et al and Tung et al reported that colorimeter had better reproducibility and reliability in measuring color difference than spectrophotometer. 19,20 ShadeEye NCC TM , which was used in this study, is one of the most advanced colorimeters with spot measurement capacity of 2.5 mm in diameter in comparison with that of 5.0 mm of other spectrophotometers. 21 Edge loss can occur when measuring shade of small tooth surface using colorimeter.…”
Section: Discussionmentioning
confidence: 99%
“…The blue and yellow axes were designated by - b * and + b * , respectively. This ShadeEye NCC® intraoral shade measuring device has been used in some previous studies with an acceptable performance 21,22. The color of all-ceramic crowns was measured using a pulsed xenon Lamp as an optical light source and a vertical light receiving system.…”
Section: Methodsmentioning
confidence: 99%